Effect of Supplementation of Turmeric and Ginger on Haemato Biochemical Profile in SVVU T17 Grower Pigs (Indian Journal of Animal Production and Management, 2024)
A study was conducted on eighteen SVVU T-17 grower pigs of 3 months age with similar body  weights, and were divided into three groups with 6 pigs in each group for a period of 60 days to study  the effect of inclusion of turmeric and ginger supplementation @ 1% in the basal diet on the haemato biochemical profile. The study revealed that among the haematological parameters Hb and PCV  exhibited significantly higher values with in the physiological range in turmeric group compared to  other groups. Among several biochemical parameters observed under the study, ALT and AST were  exhibited significant decrease in turmeric and ginger groups. Total protein, albumin, globulin levels  were in similar range with control group. Cholesterol exhibited significant decrease in turmeric and  ginger groups compared to the control group. Turmeric and ginger had hepato-protective nature and  a positive effect on overall health performance. Especially, turmeric had direct positive effect on  haemato-biochemical profile when compared to the other groups.
Keywords: SVVU T17 Grower pigs; Turmeric; Ginger; Haemato biochemical profile